Co-administration of coenzyme Q10 and curcumin mitigates cognitive deficits and exerts neuroprotective effects in aluminum chloride-induced Alzheimer's disease in aged mice - Nida Rasheed; Hafiza Khushbakht Hussain; Zohabia Rehman; Azka Sabir; Waseem Ashraf; Tanveer Ahmad; Faleh Alqahtani; Imran Imran (Experimental Gerontology)
Aluminum chloride (AlCl3), a known neurotoxic and Alzheimerogenic metal disrupts redox homeostasis which plays a pivotal role in pathophysiology of neurodegenerative disorders, particularly cognitive decline. The current study was designed to unveil the long-term neuroprotective outcomes and efficacy of CoQ10 and curcumin low dose (100 mg/kg each) combination in 18-months old geriatric male Balb/c mice subjected to AlCl3-prompted memory derangements (200 mg/kg in water bottles) for 28 days. The neuroprotective properties driven by antioxidant mechanisms were assessed via observing cellular pathology in key-memory related brain regions including the cornuammonis (CA3 and DG) and cortex 2/3 layer. Our outcomes revealed that AlCl3 exposure significantly reduced spatial learning and memory. In contrast, CoQ10 and curcumin combinatorial regime markedly mitigated cognitive deficits Vs. individual high-dose in AlCl3-treated animals as demonstrated by their improved performance in neurobehavioral tests such as the Y-maze, novel object recognition, passive avoidance and Morris-water maze test. Additionally, CoQ10 and curcumin co-administration restored redox balance by significantly reducing the levels of oxidative stressor (MDA) and increasing the anti-oxidant capacity (SOD,GPx). AchE is an enzyme involved in acetylcholine breakdown which negatively impacts acetylcholine levels and memory function. AlCl3 exposure elevated AchE levels in mice brains vs. treatment. This neurochemical alteration was notably reversed in the dual-treatment group. Furthermore, CoQ10 and curcumin ameliorated AlCl3-induced neurotoxicity by preserving neuronal cytoarchitecture in both cortical and hippocampal regions. In conclusion, CoQ10 and curcumin combination might attenuate memory loss induced by AlCl3-intoxication via restoring aberrant AchE activity, enhanced anti-oxidant defenses and salvaging the deleterious neuronal damage.